Improvement of Pedagogic Competency of Pendidikan Agama Islam and Budi Pekerti Teachers of Islamic Education by Online Learning Supervision in Cilacap District - Nurhayati, Siti (International Conference of Moslem Society, 2019)
The background of the problem of this study are: (1) the low pedagogical competence of the teacher in the making of the learning implementation plan (RPP), the implementation of the learning process and the implementation of learning evaluation; (2) the progress of communication and information technology, being realized or not, has an influence on the development of education. Such progress, inevitably drags the world of education to various changes in accordance with the needs and demands of the community; (3) improving education in the future requires information systems and information technology that not only function as supporting facilities, but rather as the main weapon to support the success of the world of education, so as to be able to compete in the global market; and (4) the importance of supervising online learning to improve the pedagogical competencies of Junior High School (SMP) teachers of the subject Pendidikan Agama Islam and Budi Pekerti in Cilacap District. Therefore, the purpose of this study is: â€œto analyze the increase in pedagogical competencies of Pendidikan Agama Islam and Budi Pekerti SMP Teacher by applying supervision of online learning in Cilacap District.â€ The design of this study uses the School Action Research (PTS) design which is a development of the design of Classroom Action Research (CAR) and carried out in four stages, namely planning, implementation, observation and interpretation, analysis and reflection, which is carried out in at least two cycles. The research location is the Working Area of the Supervisor of Islamic Education and Junior High School Characteristics in Cilacap District with the research subjects being all Teachers of Pendidikan Agama Islam and Budi Pekerti SMP in CilacapDistrict which are held for 3 (three) months, starting from January 2019 to the Month March 2019. Data collection techniques are observation and documentation, using data analysis techniques in the form of descriptive-qualitative and descriptive-quantitative. Based on several results of the study it can be concluded that the use of online learning supervision can improve the pedagogical competence of Pendidikan Agama Islam and Budi Pekerti SMP Teacher in Cilacap District. The increase occurred in: an increase in the average assessment of pedagogic competencies in the teachers of Pendidikan Agama Islam and Budi Pekerti SMP Teacher of Cilacap District, where the pre-cycle average was 62.63% with the criteria of "GOOD," then in cycle 1 it increased to 72 , 00% with the criteria of "GOOD," and finally in cycle 2 it increased again to 83.00% with the criteria "VERRY GOOD.".